BSC-based evaluation for the factors affecting the performance of wind energy companies - Dinçer, Hasan; Yüksel, Serhat; Ubay, Gözde Gülseven; Karakuş, Hüsne (Springer, 2020)
This study aims to identify the significant factors which improve the performance of wind energy companies. For this purpose, a detailed literature review is conducted, and eight different performance evaluation criteria are identified based on four dimensions of balanced scorecard (BSC) approach. In the evaluation process of these factors, fuzzy DEMATEL approach is taken into consideration. The results indicate that internal process and learning and growth are the most important dimensions of BSC regarding the wind energy investment projects. Moreover, it is also concluded that the most important criteria are technological background and research and development. Hence, it is recommended that wind energy companies should mainly pay attention to technological development in order to be successful in such a complex investment which requires high engineering knowledge. In this context, the equipment and information technology software should be effective in these countries. Owing to this issue, the risk of having deficiencies can be minimized. Additionally, high technology can be obtained with a lower cost by making extensive research and development activities.
Keywords: Energy Companies; Performance; BSC-Based